Relationships between competitive ability and pre-activation time in leg muscles during sprint running and drop jumping in college track and field athletes - Yokota, K.; Oga, R.; Tamaki, H. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Pre-activation (PA) of agonist/antagonist muscles prior to ground contact during running and jumping movements is one of the human motor control mechanisms, and according to previous reports, it has a positive impact on motor performance. There is, however, little information available regarding the relationship between the onset time of PA and subsequent motor performance in Japanese college track and field athletes. We investigated the relationships between the onset time of PA in the lower leg muscles during drop jumps (DJs), sprint running and jumping performance, and competitive ability in Japanese college track and field athletes.